PENGALAMAN KELUARGA DALAM MERAWAT DEKUBITUS - Rita Sari (JURNAL WACANA KESEHATAN, 2017)
Immobilization is a problem faced by patients with chronic illness, the patients is very weak and paralyzed patients in a long time. This study have purpose  to gain a deep understanding of the experience of families in caring for family members is immobilized with pressure sores at home. This study used qualitative methods. Participants are families who care for patients at home who are immobilized with pressure sores. Collecting data with in-depth interviews by means of instrument is the researcher's own self, written questions as an interview, used recording devices and used field notes.  Criterion sampling by taking 6 participants. Analysis of data used a phenomenological approach. The results showed that the family had a positive experience; Can be more patient, and assume that caring for a sick family member has its own challenges, being able to be with other families in caring for patients, being able to give affection and obligation as a child to parents can help take care of it. There was also an unpleasant (negative) family experience during the care of sick family members, the family felt tired, not strong and bored during patient care. The conclusion of the study is that families have positive and negative experiences in caring for family members with decubitus